Proceedings of the 8th International Nursing Conference on Education, Practice and Research Development in Nursing (INC 2017) 2017
DOI: 10.2991/inc-17.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Pediculosis capitis prevention at Islamic boarding school in Indonesia

Abstract: Abstract-Boarding school is a place where students gather to learn and stay in a dormitory. It makes boarding school become a place where diseases transmit easily, one of which is Pediculosis capitis. Various problems occur from this disease such as lack of confidence, negative social stigma, lack of sleep quality, learning disorders, and secondary infection. Although some efforts in preventing its transmission had been conducted, the incidence and negative impacts of Pediculosis capitis are still common. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The high occurrence of unhealthy behaviors (e.g., not bathing, not combing) among head lice infested people was alarming, which had also been reported by Nejati et al [27] and Nezhadali et al [28] among female students. One study in Indonesia on pediculosis preventive behaviors among female students demonstrated many respondents with mild actions had practiced moderate prevention, whereas a small proportion of respondents with bad behavior groups these avoidance had been poorly done [29]. It is consistent with the research that suggested behavioral variables have an association with the head lice infestation [3].…”
Section: Discussionsupporting
confidence: 54%
“…The high occurrence of unhealthy behaviors (e.g., not bathing, not combing) among head lice infested people was alarming, which had also been reported by Nejati et al [27] and Nezhadali et al [28] among female students. One study in Indonesia on pediculosis preventive behaviors among female students demonstrated many respondents with mild actions had practiced moderate prevention, whereas a small proportion of respondents with bad behavior groups these avoidance had been poorly done [29]. It is consistent with the research that suggested behavioral variables have an association with the head lice infestation [3].…”
Section: Discussionsupporting
confidence: 54%
“…Other studies however discovered different findings. Krisnawati [7] and a few other studies found education level of either the mother or the father to be a significant factor in the prevalence of pediculosis capitis [18,29,19,7,21,32]. In a conventional society like that Kawiley village mothers still takes upon the domestic role as the primary caregiver for her children.…”
Section: Fig-1: Kawiley Vilage (Rignolda Djamaluddin)mentioning
confidence: 99%
“…Prevalences of more than 10% to 50% were reported in Saudi Arabia 12% [3], Thailand 12,6 to 29,7%, Australia 13%, Turki Kayseri Medicine 13,3%, India 16,59% [6], Kenya 17,1%, DI Khan 20%, Karachi 25%, Peshavar 45% [3], Brazil 28 to 35% , and West Sumatra 51,92% [5]. Furthermore, there are also studies that reported more than 50% of subjects infested with human pediculus capitis those were the study done in Egypt 58.9%, Argentina 81.9% [5] Ukraine 52% [6], Jogjakarta (Indonesia) 71,3% 9 [7], Pakistan 77,4% [3], Turki 69,5%, Lybia 78% [8] and Jombang (Indonesia) 100% [9]. The studied population varied from primary school children, boarders, slum dwellers and other communities.…”
Section: Introductionmentioning
confidence: 99%